Congenital remnants as a cause of neonatal respiratory impairment - Filippo Carta; Riccardo Antonio Caria; Clara Gerosa; Sara Sionis; Melania Puddu; Giovanni Ottonello; Roberto Puxeddu (Hygeia Press di Corridori Marinella, 2017)
Neonatal respiratory distress is a potentially life-threatening condition, representing a diagnostic and therapeutic challenge for physicians, especially when it is caused by rare pathologies. Head and neck remnants are benign congenital neoplasms rarely observed in newborns. Teratoma is the most common congenital tumor in childhood, while head and neck epithelial and mesenchymal hamartomas are uncommon. We report three cases of pharyngeal congenital remnants presenting with neonatal airway obstruction. We observed a 9-month-old, 35-day-old, and 15-hour-old patients, who have been referred to our Department of Otorhinolaryngology with acute airway distress. All the patients showed a pharyngeal benign lesion, since teratomas originated from the left lateral wall of the pharynx in two cases and one "fibrovascular" hamartoma originated from the base of the tongue. Timely surgical excision through transoral CO2 laser microsurgery was curative in all the cases. Dyspnoea in newborns is a challenging condition and must be managed, when possible, by a well-trained paediatric team. When clinicians face obstructive airway congenital remnants, a timely and radical surgical excision is necessary to avoid potentially lethal asphyxia.